Pattern-Based Approach to Topology and Geometry Optimization of Steel Building Structures - Artur Lax; Sławomir Milewski (Computer Assisted Methods in Engineering and Science)
This research primarily focuses on evaluating the effectiveness of various methodologies for the topological and geometrical optimization of steel building structures through parametric descriptions. The study specifically addresses steel trusses, frames, and beams, emphasizing their integration within the broader structural system. Initial investigations have highlighted the benefits of an innovative pattern-based approach that segments the structure into distinct patterns, namely groups of structural elements subjected to localized optimization. This method effectively overcome the challenges of global parameter optimization, by providing enhanced control over local criteria and enabling a more detailed assessment of each pattern’s contribution to global optimization objectives. Building on these insights, the research seeks to advance and refine the concept of patterns, aiming to further enhance their applicability and efficiency in structural optimization.